461 SUPPRESSION OF AP4-ENHANCED EXCITATORY JUNCTIONAL POTENTIALS BY THE D3 STEREOISOMER OF A CARBOXY DERIVATIVE OF BUCKMINSTERFULLERENE. Issue 1 (1st January 2007) - Bohnstedt, B. N.; Lastfogel, J.; Hall, G.; Hasan, R.; Dugan, L.; Friedman, R. N.
Abstract : Purpose: In spinal cord injury (SCI), glutamate excitotoxicity can cause secondary injury. NMDA glutamate receptor blockade is a potential protective strategy following SCI. A crayfish neuromuscular junction (NMJ) model is useful for studying NMDA receptor activity. The D3 stereoisomer of the malonic acid (carboxy) derivative of buckminsterfullerene suppresses excitatory junctional potentials (EJPs) of NMJs of the opener muscle of crayfish ( Procambarus clarkii and simulans ) walking limbs. DL-2-amino-4-phosphonobutyric acid (AP4, a specific NMDA receptor agonist) potentiates EJPs in this preparation. This study examines whether D3 can suppress AP4-enhanced EJPs. Materials/Methods: A first or second walking limb was removed, and the meropodite and propodite were dissected to expose the excitatory axon and the opener muscle, respectively. The preparation was bathed in Van Harreveld's Solution (VH, pH 7.2 ± 0.1) for collection of pretreatment data. Following a pretreatment control, a solution of 3.75 μm AP4 in VH was applied. EJPs were recorded immediately following application and at 1 and 2 minutes, using standard intracellular electrophysiologic techniques. Short-term facilitation (10-second stimulus at 35 Hz) averaging eight tracings per second for 10 seconds was used to record EJPs. AP4/VH was then replaced with 3.75 μm AP4 and 25 μm D3 in VH. EJPs were recorded immediately and at 1, 2, 3, and 4 minutes. Post-treatment control data collection followed three complete exchanges of the bath with VH. Results: Data are reported as percent change from control amplitude; 3.75 μm AP4 enhanced EJP amplitude 30%, with a subsequent depression of 35% in 3.75 μm AP4 and 25 μm D3. The final washout returned to within 0.27% of precontrol. Qualitatively similar results were found in three additional preparations. Discussion: 25 μm D3 can suppress 3.75 μm of AP4-induced EJP potentiation. This further suggests that D3 may be a useful agent in suppressing glutamate excitotoxicity induced by NMDA receptor stimulation. Supported by the Arnold C., Barbara M. and Georgianna Fossa Spinal Cord Injury Research Fund, the IU School of Medicine Brain and Spinal Cord Injury Research Program, and the Hillblom Foundation (L.D.).